Discord Application: Turning a Voice Chat Application for Gamers into a Virtual Listening Class - Arum Nisma Wulanjani (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
Education 4.0 brings its various impact in many fields, without excluding in teaching area. The fast growth of innovations used in teaching pushes teachers to inevitably bring technologies to their classrooms. Technology is a bridge in education 4.0. By using technology appropriately in teaching process, students can have their own personal learning and achieve learning goals in such not-boring ways. In listening class, boredom is an avoidable moment. Having monotonous activities in listening class will affect students’ attitudes and response about their learning process. Introducing a new innovation to teach listening for second semester students of a university, this study tries to explore the use of discord application in their listening classes. Discord application is used to turn a conventional listening class into a virtual listening class, a monotonous listening class into an attractive listening class, and a face-to-face listening class into online-distance listening class. The finding shows that applying discord application in their listening classes can change the students’ attitude while having the listening classes. Being more active, interactive, motivated, and creative are shown by the students in the listening classes when discord application is turned on.